PENERAPAN KETERAMPILAN MENGAJAR KELOMPOK KECIL DAN PERSEORANGAN UNTUK MENINGKATKAN HASIL BELAJAR - Aini, Nurshakina; Muhammad, Marsih; Janah, Roikhatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research was motivated by the low learning outcomes of students in science subjects. This research aims to find out whether there is an increase in student learning outcomes after implementing small group and individual teaching skills in class IV of SD Negeri 09 North Pontianak. This research is quantitative research with the Classroom Action Research (CAR) type of research with two improvement cycles of the same four stages, namely: Planning, Implementation, Observation and Reflection. The results of the research concluded that there was a significant increase in student learning outcomes after applying small group and individual teaching skills in class IV C plant body material from cycle I to cycle II. In cycle I it shows a good category with an average value of student learning outcomes of 71 and a percentage of 37.5%, while in cycle II it shows a very good category with an average value of student learning outcomes of 81 and a percentage of 84.4%. This shows that there is a significant increase from cycle I to cycle II with a percentage of 46.87%.